2017
DOI: 10.3348/kjr.2017.18.4.664
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Functional Parameters and Geometric Patterns in Korean Adults on Coronary CT Angiography with a 320-Detector-Row CT Scanner

Abstract: ObjectiveTo assess the normal reference values of left ventricle (LV) functional parameters in Korean adults on coronary CT angiography (CCTA) with a 320-detector-row CT scanner, and to analyze sex-related differences and correlations with various clinical characteristics.Materials and MethodsThis study retrospectively enrolled 172 subjects (107 men and 65 women; age, 58 ± 10.9 years; body surface area [BSA], 1.75 ± 0.2 m2) who underwent CCTA without any prior history of cardiac disease. The following paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In total, 50 KJR (9101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354565758), 492 ER, and 254 Radiology articles reported original research studies analyzing patient data. Of these, 44 (88%; 95% CI: 75.8–94.8%) (910121314151617181920212324262728293031323435363738394041424344474849505152535455565758), 359 (73%; 95% CI: 68.9–76.7%), and 211 (83.1%; 95% CI: 78–87.2%) articles, respectively, revealed the start and end of data collection to the level of calendar month.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 50 KJR (9101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354565758), 492 ER, and 254 Radiology articles reported original research studies analyzing patient data. Of these, 44 (88%; 95% CI: 75.8–94.8%) (910121314151617181920212324262728293031323435363738394041424344474849505152535455565758), 359 (73%; 95% CI: 68.9–76.7%), and 211 (83.1%; 95% CI: 78–87.2%) articles, respectively, revealed the start and end of data collection to the level of calendar month.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 44 (88%; 95% CI: 75.8–94.8%) (910121314151617181920212324262728293031323435363738394041424344474849505152535455565758), 359 (73%; 95% CI: 68.9–76.7%), and 211 (83.1%; 95% CI: 78–87.2%) articles, respectively, revealed the start and end of data collection to the level of calendar month. The point estimate value of this proportion was slightly larger in KJR than in ER and Radiology, although the difference was not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 ] Another added benefit CTA has over SCA is that it can evaluate the left and/or right ventricle and/or atrium at the same time in a “one-stop shop” examination. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of LV function using CCT has been validated in prior studies via comparison with echocardiography and CMR (29). In normal Korean adults, Kang et al (30) demonstrated that the LV myocardial thickness (septal wall thickness, 1.08 ± 0.18 cm vs. 0.90 ± 0.17 cm; posterior wall thickness, 0.91 ± 0.15 cm vs. 0.78 ± 0.10 cm), LV end-diastolic volume (112.9 ± 26.1 mL vs. 98.2 ± 21.0 mL), LV end-systolic volume (41.7 ± 14.7 mL vs. 33.7 ± 12.2 mL), and mass (145.0 ± 29.1 g vs. 107.9 ± 20.0 g) were significantly greater in men than in women when using 320-detector-row CCT, even though these significant differences disappeared after normalization for body surface area. The measurement of LV functional parameters by CCT can be used as an alternative, particularly in cases of equivocal or suboptimal echocardiography or contraindications for CMR.…”
Section: Analysis Of LV Functionmentioning
confidence: 99%
“…The reference range of the LV septal and posterior wall thickness at end-diastole using echocardiography is 0.6–0.9 cm in women and 0.6–1.0 cm in men (31). In normal Korean adults, the mean LV myocardial wall thickness measured on CCT was less than 11 mm at the septum and 10 mm at the posterior wall (30).…”
Section: Wall Thicknessmentioning
confidence: 99%